Bibliometric Analysis of Research on Mathematics Anxiety in Two Decades - Irvan (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2023)
Mathematical anxiety has plagued all levels of math students. Bibliometric analysis is required due to the absence of quantitative research in this field's publications. Employing 496 Scopus literature, this research investigated the evolution of publications pertinent to mathematics anxieties in learning. The descriptive and network analysis software applications Biblioshiny and VOSviewer are utilized. Over the past 20 years, the results demonstrate that the aggregate trend of publications in this field has increased by 25% annually. Frontiers in Psychology is ranked first among publications. The most influential author, E.A. Maloney, had 832 citations and publications. The United States surpassed all other nations in terms of contribution. The article